Thermomechanical measurements for a flat-type divertor mock-up: A benchmark for simulation - Menglai Jiang; Zhiwei Pan; Shenghong Huang; Zhanru Zhou; Yong Su (Nuclear Materials and Energy, 2023)
The divertor is a key component of plasma facing components (PFCs). Its servicing lifetime under high heat flux (HHF) loadings seriously affects the operating time of the nuclear fusion reactor. Therefore, it is of great significance to study the thermomechanical behavior of the divertor and its fabricating materials under HHF loadings to optimize its design. However, it lacks benchmark measurements on the thermal deformation, strain and fractures of components under servicing conditions to validate simulations. In this paper, a thermomechanical benchmark model of a flat-type divertor mock-up is established, which is based on a series of HHF loading experiments with heat flux magnitudes of 1 ∼ 15 MW/m2. The thermomechanical measurements, including surface temperature, surface displacements and strain components, under HHF loading conditions are obtained with both infrared thermal imaging and digital image correlation (DIC) techniques. With postprocessing of decoupling thermal/mechanical strains, the cumulative equivalent mechanical strain at points of interest and thus their low cycle fatigue lifetime is evaluated according to measured data, which can be used as benchmark datasets for related numerical simulations. Several interesting findings involving heat transfer modes, thermomechanical responses and the corresponding fatigue lifetime change patterns were also discussed.